Ethical Challenges of Germline Genetic Enhancement - Macpherson, Ignacio; Roqué, María Victoria; Segarra, Ignacio (Frontiers in Genetics, 2019)
The new reproductive technologies have opened the door to different processes of germline genetic enhancement by which the characteristics of an individual according to the interests of the agents involved could be selected during its gestation. Although the initiative is apparently oriented towards developing individuals that would excel in society, critical voices raise the concerns about that this approach would generate and need for a reflection on the ethical, social and legal implications of these techniques and their implementation in society. We reviewed the literature about these issues throughout their historical records to date, focusing on the moral arguments and non-clinical aspects that affect the legal and social environment. We have observed various trends of thought with divergent positions (proactive, preventive, and regulatory) as well as a large number of articles that try to reconcile the different approaches. This review illustrates a series of concepts from the ethics and philosophy fields which are frequently used in studies that evaluate the ethical implications of germline genetic enhancement, such as dignity, benefit, autonomy, and identity. In addition, amongst the many unresolved controversies surrounding genetic enhancement, we identify procreative beneficence, genetic disassociation, gender selection, the value of disability, embryo chimerization, and the psychosocial inequality of potentially enhanced individuals as crucial. We also develop possible scenarios for future debate. We consider especially important the definition and specification of three aspects which are essential for the deployment of new reproductive technologies: the moral status of the embryo undergoing enhancement, the legal status of the enhanced individual, and the responsibility of the agents executing the enhancement. Finally, we propose the precautionary principle as a means to navigate ethical uncertainties.